2018
DOI: 10.1159/000487222
|View full text |Cite|
|
Sign up to set email alerts
|

Newborn Plasma Glucose Concentration Nadirs by Gestational-Age Group

Abstract: Background: The glucose concentrations and times to nadir for newborns of all gestational ages when intrapartum glucose-containing solutions are not routinely provided are unknown. Objective: To characterize and compare patterns of initial glucose concentration nadirs by gestational-age groups. Methods: A cross-sectional cohort study of 1,366 newborns born in 1998 at the University of Arkansas for Medical Sciences, appropriate for gestational age, nonasphyxiated, nonpolycythemic, and not infants of diabetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…We appreciate and agree with the comments by Hay et al [1] regarding our paper, “Newborn Plasma Glucose Concentration Nadirs by Gestational-Age Group” [2]. In this study, we showed for the first time that glucose concentration nadirs for extremely low gestational age newborns (ELGANs) as well as for preterm and late preterm newborns were lower than those for full term newborns and that the time to nadir for ELGAN and preterm newborns was significantly earlier than for full term newborns.…”
supporting
confidence: 73%
“…We appreciate and agree with the comments by Hay et al [1] regarding our paper, “Newborn Plasma Glucose Concentration Nadirs by Gestational-Age Group” [2]. In this study, we showed for the first time that glucose concentration nadirs for extremely low gestational age newborns (ELGANs) as well as for preterm and late preterm newborns were lower than those for full term newborns and that the time to nadir for ELGAN and preterm newborns was significantly earlier than for full term newborns.…”
supporting
confidence: 73%
“…Harris et al reported an incidence of 51% in infants ≥ 35 weeks' gestation within the first 48 h after birth (1). A recent study reported that the nadir of plasma glucose concentration in preterm infants and extremely preterm infants is after 70.5 and 60.9 min, respectively (15). Our glucose samples were taken at a mean postnatal age of 49.4 min, potentially missing the nadir of hypoglycemia and resulting in underestimation of our incidence.…”
Section: Discussionmentioning
confidence: 81%
“…In their just published article in Neonatology [1], the authors conclude their abstract with the following sentence: “In order to potentially prevent low glucose concentrations at the time of the nadir, exogenous glucose should be provided to all newborns as soon as possible after birth.” We should like to point out that this statement is factually incorrect, misleading, and potentially harmful. If “all” newborns were to receive exogenous glucose, this would apply to the vast majority of term and even many late preterm infants who appropriately do not receive exogenous glucose and normally suckle ad lib.…”
mentioning
confidence: 99%